Long-term effects of row orientation on oil yield and oil yield components of hedgerow olive orchards cv. Arbequina - Gómez del Campo, María; Trentacoste, Eduardo Rafael; Connor, David J. (Elsevier, 2022)
Orchardists are adopting hedgerow systems of many horticultural tree crops to benefit from early and higher yield and to facilitate mechanical pruning and harvesting for more timely management at lower cost. In the case of olive, guidance in orchard design is available for the dimensions (height and width), spacing and porosity of hedgerows of the dominant super-high density (SHD) design but less so for hedgerow orientation. An analysis is presented of oil yield and its components of four olive hedgerows orchards (N–S, E–W, NE–SW and NW–SE) maintained at optimum dimensions during 7 years from the third year after planting. Oil yield was highly variable from year to year in a range 1.7–3.6 t oil/ha but average yield of NE–SW, although not different from NW–SE and N–S, was significantly greater than E–W by 12%. Yield of NE–SW exceeded those of other orientations in two of the seven years of observation by increase in fruit number without effect on fruit size or oil concentration. Analysis of the impact of orientation on yield excludes annual interception of solar radiation as an explanation because NE–SW has similar interception to NW–SE and N–S but greater yield. This identifies the importance of seasonal, and possibly diurnal, differences in radiation interception and associated microclimatic factors of temperature, VPD and water stress. In olive, determination of fruit number is a long stepwise process that commences in autumn with bud initiation and continues with bud formation, flowering, fruit set and fruit fall in the following spring. Concentration of effort on the role of orchard design and management in determination of fruit number emerges as the most useful step in unraveling the role of hedgerow orientation and yield variability in olive production systems.